2020
DOI: 10.2147/ott.s235349
|View full text |Cite
|
Sign up to set email alerts
|

<p>Safety and Efficacy of Chemotherapy Combined with Anlotinib Plus Anlotinib Maintenance in Chinese Patients with Advanced/Metastatic Soft Tissue Sarcoma</p>

Abstract: Purpose: Anlotinib, a newly developed oral small-molecule receptor tyrosine kinase inhibitor (TKI), has been shown to have encouraging activity against sarcoma. The purpose of this study was to retrospectively evaluate the safety and clinical efficacy of chemotherapy combined with anlotinib plus anlotinib maintenance in advanced/metastatic soft tissue sarcoma (STS) patients in a real-world setting in China. Patients and Methods: We retrospectively collected the medical data of thirty-two patients with advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
(36 reference statements)
9
34
0
Order By: Relevance
“…In so-doing, it effectively suppresses tumor angiogenesis and growth, with acceptable toxicity as seen in lu ng squamous cell carcinoma, advanced lung adenocarcinoma, small cell lung cancer, soft tissue sarcoma, medullary thyroid cancer, and metastatic renal clear cell cancer (Han et al, 2018;Sun et al, 2018;Shao et al, 2019;Yang et al, 2019;Zhou et al, 2019). Its major side effects include fatigue, high blood pressure, hand-foot skin reaction, gastrointestinal reactions, triglyceride elevation cholesterol elevation, and blood thyrotrophin elevation (Sun et al, 2016;Shao et al, 2019;Wang et al, 2020). To rule out other factors contributing this patient's hypertensive retinopathy, such as possible drug interactions, diet, and congenital factors, a detailed medical history was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In so-doing, it effectively suppresses tumor angiogenesis and growth, with acceptable toxicity as seen in lu ng squamous cell carcinoma, advanced lung adenocarcinoma, small cell lung cancer, soft tissue sarcoma, medullary thyroid cancer, and metastatic renal clear cell cancer (Han et al, 2018;Sun et al, 2018;Shao et al, 2019;Yang et al, 2019;Zhou et al, 2019). Its major side effects include fatigue, high blood pressure, hand-foot skin reaction, gastrointestinal reactions, triglyceride elevation cholesterol elevation, and blood thyrotrophin elevation (Sun et al, 2016;Shao et al, 2019;Wang et al, 2020). To rule out other factors contributing this patient's hypertensive retinopathy, such as possible drug interactions, diet, and congenital factors, a detailed medical history was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, chemotherapy combined with anlotinib plus anlotinib maintenance therapy showed good efficacy and resulted in more favorable survival with good tolerance in advanced soft tissue sarcoma[ 18 ]. For the first time, we report the effects of NAC combined with anlotinib in the treatment of OBC.…”
Section: Discussionmentioning
confidence: 99%
“…Anlotinib also has encouraging antitumor effects and acceptable toxicity in advanced NSCLC, small cell lung carcinoma, medullary thyroid cancer, soft tissue sarcomas and metastatic renal clear cell cancer. [24][25][26][27][28] A multicenter, double-blind, Phase III randomized clinical trial (ALTER 0303) of patients with advanced NSCLC who progressed after second-line or later treatment showed that compared with the placebo group, the anlotinib group had a significantly longer PFS (5.4 vs 1.4 months; P < 0.001) and OS (9.6 vs 6.3 months; P < 0.001) and a higher ORR (9.2% vs 0.7%; P < 0.001) and DCR (81.0% vs 37.1%; P < 0.001). 18 As a novel multitargeted kinase inhibitor, anlotinib, which inhibits not only tumor cell proliferation but also tumor angiogenesis, is the first drug approved in China as third-line therapy for metastatic/advanced NSCLC.…”
Section: Discussionmentioning
confidence: 99%